Baseline adiponectin concentration and clinical outcomes among patients with diabetes and recent acute coronary syndrome in the EXAMINE trial. Issue 7 (17th March 2017) - Bergmark, Brian A.; Cannon, Christopher P.; White, William B.; Jarolim, Petr; Liu, Yuyin; Bonaca, Marc P.; Zannad, Faiez; Morrow, David A.
Abstract : Aim: To investigate adiponectin levels and cardiovascular (CV) outcomes in patients with diabetes and recent acute coronary syndrome (ACS). Materials and methods: We analysed baseline adiponectin concentration and CV outcomes in 5213 patients with type 2 diabetes enrolled in the EXAMINE trial of alogliptin vs placebo 15 to 90 days (median 45 days) after ACS. Event rates at 18 months are reported. Results: The median (interquartile range) baseline adiponectin concentration was 5.2 (3.5‐7.9) μg/mL. Patients with the highest baseline adiponectin concentration (quartile [Q]4) were at significantly higher risk of death from a CV event (8.4% vs 1.7%; P  < .0001), hospitalization for heart failure (HF; 7.5% vs 1.7%; P  < .0001), and all‐cause mortality (10.8% vs 2.4%; P  < .0001) compared with those in Q1. After adjusting for age, sex, index event, HF, estimated glomerular filtration rate and hypertension, adiponectin concentration in Q4 remained associated with an increased risk of death from CV causes (hazard ratio [HR] 2.43, 95% confidence interval [CI] 1.52, 3.88), all‐cause mortality (HR 2.45, 95% CI 1.65, 3.64), and HF (HR 2.44, 95% CI 1.47, 4.05), without change after stratification by body mass index. There was no significant difference in the rate of myocardial infarction or stroke. Conclusions: In this contemporary population of patients with diabetes and ACS, adiponectin concentration was independently associated with increased risk of death from CV causes, all‐cause mortality, and hospitalization for HF. The relationship between adiponectin and CV outcomes is complex and deserves further study.